Factors Affecting Liquidity in Indonesian Sub Sector Metal Industries - Hantono Hantono; Teng Sauh Hwee (Universitas Sebelas Maret, 2018)
The purpose of this research is to verify and analyze the factors that affect the liquidity in sub-sector metal industries listed on Indonesia Stock Exchange (IDX). We purposively use 10 firms out of 16 firms because of these 16 firms does not meet our criteria. This paper comprehensively investigates step-by-step of statistical analysis from classical assumption testing such as normality, heteroscedasticity, autocorrelation, and multicollinearity and then continued by testing model and variables using t-test and F-test. our testing result shows that we do not have problem of classical assumptions. We also find that net working capital turnover, account receivable turnover and inventory turnover significantly affect firm liquidity.